THE ROLE OF REWARD AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE IN PUBLIC SERVICE ORGANIZATIONS AFTER COVID-19: A CASE STUDY OF MINISTRY OF FINANCE - Imam Subhan; Yos Sunitiyoso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study delves into the relationship between rewards, career development, and employee performance within the Ministry of Finance of Indonesia (MoF), amidst the challenges posed by the COVID-19 epidemic. Employing a path analysis, perspectives from 100 MoF workers are examined, revealing noteworthy findings that contribute significantly to the understanding of these relationships. Notably, a clear and statistically significant correlation between rewards and employee performance is identified, alongside a favorable direct correlation between career development and rewards. Importantly, there is no statistically significant evidence indicating a direct influence of career development on employee performance. Through indirect analysis, rewards emerge as a mediating factor, exerting no significant impact between career development and employee performance. This study provides a scholarly contribution by offering insights into the adaptations made to HRM practices within the financial public services sector in response to the pandemic's effects. The findings hold considerable practical implications, furnishing insights for public organizations to strategically manage their incentive systems and career development programs, as well as comprehend the complex interrelationships among these factors. Public organizations seeking to enhance their HRM practices can derive guidance offered by this study, serving as a resource on cultivating a resilient and productive workforce in the post-COVID-19.